Implementasi Persetujuan Lingkungan dalam Kemudahan Perizinan Berusaha dan Dampaknya terhadap Perlindungan dan Pengelolaan Lingkungan - Cut Nova Rida (Seminar Nasional Lahan Suboptimal, 2021)
Rida CN. 2021. Implementation of the environmental approval in the ease of business license and the impactson environmental protection and management. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 376-383.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The Draft Job Creation Law was officially ratified in the plenary session of the DPR on October 5, 2020. (Amania, 2020) There are several important points in the amendment of Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management, namely from the original Environmental Permit that was changed become an environmental feasibility decision (Environmental Approval) which is a requirement in business licensing. As well as implementing regulations related to technical approvals for Fulfillment of Wastewater Quality Standards, Compliance with Emission Quality Standards, B3 Waste Management, and Analysis of Traffic Impacts. This study aims to find out how the implementation of environmental approvals in providing ease of licensing for companies that are just about to operate so that these regulations provide warnings and vigilance to business activities, especially those that have high risks to health, safety, and the environment. In this research, the writer uses descriptive analysis study method which is quantitative. The results of the study stated that the renewal of the Law on Environmental Management and its derivatives was influenced by various developments and changes that occurred in society, such as the influence of the era of democratization, industrialization, advances in science and technology and the increasing demand for welfare from various parties, so that information on environmental documents must be integrated into a risk-based Business Licensing (OSS RBA) in Government Regulation no. 22 of 2021, there are 3 for the main prerequisite in making a decision to grant a permit for a business and activity which explains in detail the prerequisites for environmental approval.